2018
DOI: 10.1016/j.ijnonlinmec.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear axisymmetric vibrations of a hyperelastic orthotropic cylinder

Abstract: In this paper we investigate the large-amplitude axisymmetric free vibrations of an incompressible nonlinear elastic cylindrical structure. The material behavior is described as orthotropic and hyperelastic using the physically-based invariants proposed by Rubin and Jabareen (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 39 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…In ( 9)- (10), the strict inequality ">" is replaced by "≥" if any two principal stretches are equal.…”
Section: Stochastic Isotropic Incompressible Hyperelastic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ( 9)- (10), the strict inequality ">" is replaced by "≥" if any two principal stretches are equal.…”
Section: Stochastic Isotropic Incompressible Hyperelastic Modelsmentioning
confidence: 99%
“…Radial oscillations of cylindrical tubes and spherical shells of neo-Hookean [102], Mooney-Rivlin [69,82], and Gent [32] hyperelastic materials were analysed in [15,16], where it was inferred that, in general, both the amplitude and period of oscillations decrease when the stiffness of the material increases. The influence of material constitutive law on the dynamic behaviour of cylindrical and spherical shells was also examined in [8,10,84,110], where the results for Yeoh [109] and Mooney-Rivlin material models were compared. In [19], the static and dynamic behaviour of circular cylindrical shells of homogeneous isotropic incompressible hyperelastic material modelling arterial walls were considered.…”
Section: Introductionmentioning
confidence: 99%
“…A visco-hyperelastic model was presented by Zhao et al [141] for modelling the chaotic motion of spherical shells. Other studies on the dynamic behaviour of hyperelastic plates and shells can be found in refs [142][143][144][145][146][147][148], emphasising the importance of considering hyperelasticity in studying the dynamic response of such structures. Studies on the nonlinear dynamics of hyperelastic plates and shells are summarised in Table 2.…”
Section: Nonlinear Dynamics Of Hyperelastic Plates and Shellsmentioning
confidence: 99%
“…Wang and Zhu [26] investigated the nonlinear vibrations of a hyperelastic beam under time-varying axial loading are derived via the extended Hamilton's principle. Iglesias et al [27] studied the large-amplitude axisymmetric free vibration of an incompressible hyperelastic orthotropic cylinder, and analyzed the influence of initial conditions, structural and material parameters on the dynamic behavior. With the Gent-Gent hyperelastic model, Alibakhshi and Heidari [28] researched the nonlinear vibration of a dielectric elastomer balloon considering the strain hardening and the second invariant of the Cauchy-Green deformation tensor, and found that the second invariant parameter could suppress the chaotic motion of the system.…”
Section: Introductionmentioning
confidence: 99%